2014
DOI: 10.17221/167/2013-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ultraviolet, visible, and near infrared spectroscopy for the analysis of wine compounds

Abstract: Martelo-Vidal M.J., Vázquez M. (2014): Evaluation of ultraviolet, visible, and near infrared spectroscopy for the analysis of wine compounds. Czech J. Food Sci., 32: 37-47.Spectroscopy of UV-VIS-NIR combined with chemometric analyses was used as a non-destructive technique to build models for the quantitative characterisation of the main compounds of wine. The work in mixtures can give insight into how interferences affect the performance of calibrations in wines. Ethanol, glycerol, glucose, tartaric acid, mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Several studies have focused on near infrared control during the L-(+)-lactic acid production (GONZÁLEZ-VARA et al, 2000), monitoring of fermentation processes for Lactobacillus fermentum ES15 (TOSI et al, 2003), or FT-MIR and FT-Raman spectroscopic techniques in Lactobacillus casei fermentation from media containing only glucose at varying concentrations as carbon sources (SIVAKESAVA et al, 2001). Quantitative infrared spectroscopy has also been used for monitoring glucose and gluconic acids (FRANCO et al, 2006) or for lactic acid production from whey (TRIPATHI et al, 2015), for organic acids determination in fruit vinegars (LIU et al, 2011), wine (REGMI et al, 2012MARTELO-VIDAL & VÁZQUEZ, 2014a), fruit (BUREAU et al, 2009), and tomatoes (BEULLENS et al, 2009), as well as for detection of polyphenolic compounds from red wine (MARTELO-VIDAL & VÁZQUEZ, 2014b) and nutritional compounds determination from yogurt (MOROS et al, 2006) and cheese (SUBRAMANIAN et al, 2011). Most of these quantitative determinations were validated by multivariate statistics or chemometrics.…”
mentioning
confidence: 99%
“…Several studies have focused on near infrared control during the L-(+)-lactic acid production (GONZÁLEZ-VARA et al, 2000), monitoring of fermentation processes for Lactobacillus fermentum ES15 (TOSI et al, 2003), or FT-MIR and FT-Raman spectroscopic techniques in Lactobacillus casei fermentation from media containing only glucose at varying concentrations as carbon sources (SIVAKESAVA et al, 2001). Quantitative infrared spectroscopy has also been used for monitoring glucose and gluconic acids (FRANCO et al, 2006) or for lactic acid production from whey (TRIPATHI et al, 2015), for organic acids determination in fruit vinegars (LIU et al, 2011), wine (REGMI et al, 2012MARTELO-VIDAL & VÁZQUEZ, 2014a), fruit (BUREAU et al, 2009), and tomatoes (BEULLENS et al, 2009), as well as for detection of polyphenolic compounds from red wine (MARTELO-VIDAL & VÁZQUEZ, 2014b) and nutritional compounds determination from yogurt (MOROS et al, 2006) and cheese (SUBRAMANIAN et al, 2011). Most of these quantitative determinations were validated by multivariate statistics or chemometrics.…”
mentioning
confidence: 99%
“…According to [1,[14][15], the maximum absorption spectrum for ethanol at ultraviolet wavelength was identified at 205nm, 210nm and 304nm respectively. Besides that, in [2] states 202nm, 228 nm and 300nm were identified also as ethanol absorption spectrum. However, the finding found in this research study is a bit shifted away from the reported literature.…”
Section: K a Rahman Et Al J Fundam Appl Sci 2017 9(4s) 384-400mentioning
confidence: 99%
“…Nowadays, spectroscopy techniques has received much attentions in investigating the ethanol compound at Ultraviolet (UV) [1][2], Near-infrared [3][4] and Mid-Infrared (MIR) wavelength regions [5][6][7]. Spectroscopy offers repeatable and reliable results and has simple sample as compared to fiber optic sensors which is fragile and tedious to be fabricated [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…4D) were 2.55-5.11% v/v (~32.32-64.77 × 10 3 mg/ L). This volatile compound shows a UV spectrum from 200 to 300 nm [35] and it can cause displacement of the UV-Vis absorption spectra related to other solutes of the mixture due to change in solvent polarity, [36] but this phenomenon should not influence the original spectral data because of the sample dilution factor (40-fold).…”
Section: Uv-vis Absorption Spectra Of Beer Samplesmentioning
confidence: 99%